Pengaruh Ukuran Perusahaan Dan Kepemilikan Manajerial Terhadap Kinerja Keuangan Dengan Pertumbuhan Perusahaan Sebagai Variabel Moderating Pada Perusahaan Pertambangan - Sherlinda Tryani; Lusiana Lusiana; Putri Azizi (Universitas 45 Surabaya, 2024)
This study aims to describe and estimate the effect of company size and managerial ownership on financial performance with company growth as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The population of this study were 64 mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sample in this study was taken using purposive sampling technique with a total of 33 companies. The analysis technique used is panel data regression analysis with the help of the Eviews-12 program. Based on the results of partial hypothesis testing, Company Size has a positive and significant effect on Financial Performance, partially Managerial Ownership has no effect on Financial Performance. Company Size has a positive and significant effect on Financial Performance with moderation by Company Growth, and Managerial Ownership has no effect on Financial Performance with Company Growth as a Moderating Variable.